Guide to managing growth : turning success into even bigger success - Merson, Rupert (London : The Economist in association with Profile Books, 2011)
Growth, and the change it brings, affects every aspect of the business - people management, marketing, customer and client management, financial management, organisational design, performance management and measurement. This guide explores the different aspects of growth and outlines strategies and tactics that will enable businesses to address the issues they face and move forward to a bigger and even more successful future.
Includes bibliographical references (p. [213]-215) and index.
Keywords: Organizational change -- Management; Business enterprises